Transendothelial migration: unifying principles from the endothelial perspective. Issue 1 (September 2016) - Muller, William A.
Summary: Transendothelial migration (TEM) of polymorphonuclear leukocytes (PMN) involves a carefully orchestrated dialog of adhesion and signaling events between leukocyte and endothelial cell. This article focuses on the contribution of endothelial cells to transmigration. The initiation of TEM itself generally requires interaction of PECAM on the leukocyte with PECAM at the endothelial cell border. This is responsible for the transient elevation of cytosolic‐free calcium ions in endothelium that is required for TEM and for recruitment of membrane from the lateral border recycling compartment (LBRC). TEM requires LBRC to move to the site at which TEM will take place and for VE‐cadherin to move away. Targeting of the LBRC to this site likely precedes movement of VE‐cadherin and may play a role in clearing VE‐cadherin from the site of TEM. The process of TEM can be dissected into steps mediated by distinct pairs of PMN/endothelial interacting molecules. CD99 regulates a step at or close to the end of TEM. CD99 signals through soluble adenylyl cyclase to activate PKA to trigger ongoing targeted recycling of the LBRC. Paracellular transmigration predominates (≥90% of events) in the cremaster muscle circulation, but transcellular migration may be more important at sites such as the blood‐brain barrier. Both processes involve many of the same molecules and recruitment of the LBRC.